Analysis of The Implementation of Smoke-Free Policies in Government Work Environments: A Case Study of the Cirebon City Education Office - Nugraha, Adi; Nugraha, Noval; Khumayah, Siti; Rohida, Leni (ann4publisher@gmail.com, 2025)
Background. Smoking behavior remains one of the most significant public health issues in Indonesia. The country ranks third in the world in terms of the number of smokers, after China and India. According to the Global Adult Tobacco Survey (GATS, 2021) report, the prevalence of adult smokers in Indonesia reaches 34.5 percent or around 70.2 million people, of which 65.5 percent are men and only 3.3 percent are women, indicating a significant gender gap in smoking behavior (Tjandrarini et al., 2021). Aims. This study aims to analyze the implementation of the Smoke-Free Zone (SFZ) policy in government work environments, particularly at the Cirebon City Education Office, focusing on supporting factors, obstacles, and the level of policy effectiveness. Methods. The method used is a qualitative case study, supported by direct observation and document analysis. In-depth interviews were conducted with ten key informants, including structural officials, staff, and supervisors. Result. The main problem in this study was the low level of compliance with the policy despite the issuance of regulations requiring it. The study showed that the Mayor's Circular Letter and no smoking signs had disseminated the SFZ policy normatively. Due to a lack of supervision, employee awareness, and clear sanctions, implementation has not gone well. Conclusion. Factors supporting implementation include leadership commitment and the availability of legislation, while factors hindering implementation include a strong smoking culture, limited supervisory resources, and a lack of designated smoking areas. Because the policy has not been consistently implemented, SFAs (Smoke-Free Areas) in the Cirebon City Education Office remain ineffective. Implementation. Recommendations include increasing education-based socialization, implementing administrative sanctions, and providing facilities in accordance with local regulations on SFAs.